Associations of Trimester-Specific Exposure to Bisphenols with Size at Birth: A Chinese Prenatal Cohort Study - Hu, Jie (Environ Health Perspect, 2019)
BACKGROUND: Bisphenol A (BPA) is an endocrine disruptor that affects fetal growth in experimental studies. Bisphenol F (BPF) and bisphenol S (BPS), which have been substituted for BPA in some consumer products, have also shown endocrine-disrupting effects in experimental models. However, the effects of BPF and BPS on fetal growth in humans are unknown. OBJECTIVES: Our goal was to investigate trimester-specific associations of urinary concentrations of BPA, BPF, and BPS with size at birth. METHODS: The present study included 845 pregnant women from Wuhan, China (2013–2015), who provided one urine sample in each of the first, second, and third trimesters. Linear regressions with generalized estimating equations were applied to estimate trimester-specific associations of urinary bisphenol concentrations with birth weight, birth length, and ponderal index. Linear mixed-effects models were used to identify potential critical windows of susceptibility to bisphenols by comparing the exposure patterns of newborns in the 10th percentile of each birth anthropometric measurement to that of those in the 90th percentile. RESULTS: Medians (25th–75th percentiles) of urinary concentrations of BPA, BPF, and BPS were 1.40 (0.19–3.85), 0.65 (0.34–1.39), and 0.38 (0.13–1.11) ng/mL, respectively. Urinary BPA concentrations in different trimesters were inversely, but not significantly, associated with birth weight and ponderal index. Urinary concentrations of BPF and BPS during some trimesters were associated with significantly lower birth weight, birth length, or ponderal index, with significant trend p-values ([Formula: see text]) across quartiles of BPF and BPS concentrations. The observed associations were unchanged after additionally adjusting for other bisphenols. In addition, newborns in the 10th percentile of each birth anthropometry measure had higher BPF and BPS exposures during pregnancy than newborns in the 90th percentile of each outcome. CONCLUSIONS: Prenatal exposure to BPF and BPS was inversely associated with size at birth in this cohort. Replication in other populations is needed. https://doi.org/10.1289/EHP4664